How Do Our Values Inform Ethical Research? A Narrative of Recognizing Colonizing Practices - Dzidic, Peta; Bishop, Brian John (Springer, 2017)
© Society for Community Research and Action 2017 How do you reconcile tensions between ethical research practice, personal values, and disciplinary values? This article focuses on an ethical challenge involving the engagement of rural Indigenous community members that emerged during my PhD fieldwork. The narrative illustrates the necessity to engage in critical reflexive research practice, a process which saw me respond to my own feelings of “wrong” and “right,” contemplate a distinction between procedural ethics and virtue ethics in community-based research, explore colonizing research practices, and endeavor to reconcile an instance where the values of community psychology appeared in contest. The “voice” in this narrative is that of the first author; the dual authorship reflects the ongoing collaboration between both authors. When this ethical issue came about, our relationship was one of “student” and “supervisor”; we are now colleagues and friends.